Metaforyka zdrowia w listach Augustyna - Marciniak, Bernard Jarosław (Vox Patrum, 2019)
Augustin in his correspondence many times uses the metaphor based on medicine and hygiene – deeply rooted in biblical, patristic and philosophical tradition of his times. Directly or indirectly he refers mainly to two ideas: Christ as Medical Doctor and St. Paul’s doctrine of the Church as the Body of Christ. Christians are members of the Church. Their personal sins, spiritual flaws, foreign doctrines and heresies they are attracted to, schisms they join such as Judaism. Priscilianism, Manicheism, Donatism, paganism, pride and discord among communities are all presented metaphorically as illnesses. Augustine uses the images of blindness, cancer, gangrene, madness, lethargy, dementia and injury. The Author as the Shepherd of the Church offers various devices and ways to fight the vices, using medical terms in a didactic context. In this way, medicine becomes the representation of the Church’s discipline, ethics and spirituality.